Therapy for persistent hyperinsulinemic hypoglycemia of infancy. Understanding the responsiveness of beta cells to diazoxide and somatostatin. - Kane, C (1997)
The neonatal disorder persistent hyperinsulinemic hypoglycemia of infancy (PHHI) arises as the result of mutations in the subunits that form the ATP-sensitive potassium (KATP) channel in pancreatic beta cells, leading to insulin hypersecretion. Diazoxide (a specific KATP channel agonist in normal beta cells) and somatostatin (octreotide) are the mainstay of medical treatment for the condition. To investigate the mechanism of action of these agents in PHHI beta cells that lack KATP currents, we applied patch clamp techniques to insulin-secreting cells isolated from seven patients with PHHI. Five patients showed favorable responses to medical therapy, and two were refractory. Our data reveal, in drug-responsive patients, that a novel ion channel is modulated by diazoxide and somatostatin, leading to termination of the spontaneous electrical events that underlie insulin hypersecretion. The drug-resistant patients, both of whom carried a mutation in one of the genes that encode KATP channel subunits, also lacked this novel K+ channel. There were no effects of diazoxide and somatostatin on beta cell function in vitro. These findings elucidate for the first time the mechanisms of action of diazoxide and somatostatin in infants with PHHI in whom KATP channels are absent, and provide a rationale for development of new therapeutic opportunities by K+ channel manipulation in PHHI treatment.